A new minisatellite VNTR marker, Pscp1, discovered for the identification of opium poppy. (November 2021) - Chang, Miwha; Lee, Eun-jung; Kim, Joo-Young; Lee, Haeyong; Choe, Sanggil; Moon, Seohyun
Abstract: Opium poppy, a member of the Papaveraceae family, is an ancient herbaceous plant and well-known medical resource in the pharmaceutical industry. However, opium poppies are grown worldwide for producing illicit drugs, significantly increasing the incidence of narcotic drug abuse. Since the narcotic poppy has not yet been genetically investigated, we characterized a novel variable number tandem repeat (VNTR) marker of forensically important poppy species based on the genetic analysis of 164 samples collected from two locations spanning the Jeolla province and Jeju island of South Korea. Comparing analysis of the chloroplast (cp) genome sequences for four representative species of Papaver ( Papaver somniferum, Papaver somniferum subs. setigerum, Papaver orientale, and Papaver rhoeas ) revealed a unique region with 1–3 repeats for 16 nucleotide motifs in the genome inverted repeat A (IRA, positions 128, 651 to 128, 698) region. For 16 nucleotide motifs, 3 repeats were found in P. somniferum, and 2 repeats were found in P. somniferum subs. setigerum . Therefore, 10 known and the 133 unknown, seized Papaver species were compared to determine whether the species could be identified via variations in the repeat units. The sizes of a novel VNTR ranged from 181 to 252 bp between the species. Phylogenetic analysis confirmed that a novel VNTR, which we named Pscp1, could clearly distinguish between the narcotic and non-narcotic types of Papaver species based on the patterns of sequence variation. Interestingly, we found that Pscp1 could also distinguish between P. somniferum and P. somniferum subs. setigerum . The regions of eight non-narcotic species displayed similar patterns and also differences were found due to the nucleotide substitution and deletion events. The structural differences of Pscp1 were observed within the two narcotic species or between the narcotic and non-narcotic species, suggesting that these variations may act as a genetic marker. We, therefore, developed a new Pscp1 PCR-capillary electrophoresis (CE) method that can reliably identify the narcotic type of Papaver species. Taken together, our findings suggest that the newly developed Pscp1 can be used as an identification marker of opium poppy, and establish that the Pscp1 genotyping method by PCR-CE is an effective primary screening tool that can also contribute to species discrimination in the field of forensic diagnosis and applications. Highlights: The novel VNTR Pscp1 varies between 181 and 252 bp sizes in various Papaver species. Pscp1 has two variants differing in the number of repeats and deletion events. Pscp1 shows structural variation owing to species-specific length polymorphism. Pscp1 distinguishes the narcotic and non-narcotic types of Papaver species. The new PCR-CE method using Pscp1 validates the narcotic types of Papaver species.